2018
DOI: 10.1016/j.talanta.2018.02.098
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antioxidant capacity of thiol-containing compounds by electron spin resonance spectroscopy based on Cu2+ ion reduction

Abstract: Electron spin resonance spectroscopy was applied to determining the antioxidant capacity of eight thiol-containing compounds, including reduced glutathione, N-acetyl-L-cycsteine, methimazole, captopril, and tiopronin with one thiol group, 1,4-dithioerythritol and 2,3-dimercapto-1-propanol with two thiol groups, as well as L-cystine with no free thiol group. Cu ion gives an electron spin resonance signal and is reduced to Cu ion with no electron spin resonance signal by the free thiol group in the compounds. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Based on natural thiol-containing antioxidant compounds, it was suggested that a sulfhydryl group in addition to a phenolic hydroxyl group and conjugated double bonds can increase the antioxidant capacity (Devasagayam et al 1991;Jiang et al 2018). The second part of our study was thus concerned with coniferyl thiol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on natural thiol-containing antioxidant compounds, it was suggested that a sulfhydryl group in addition to a phenolic hydroxyl group and conjugated double bonds can increase the antioxidant capacity (Devasagayam et al 1991;Jiang et al 2018). The second part of our study was thus concerned with coniferyl thiol.…”
Section: Resultsmentioning
confidence: 99%
“…Coniferyl thiol, as substituted allyl thiol, is considered to be a bioactive product and a key intermediate for the synthesis of multifunctional sulfur-containing polyphenolic derivatives. Also, it is a free radical scavenger and a reductant due to the reducing ability of its thiol group (Jiang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al . () examined the antioxidant capacity of eight thiol‐containing compounds by electron spin resonance spectroscopy, and found that the activity of these compounds was significantly correlated with the amount of free sulfhydryl bonds presenting in the molecules. de Almeida et al .…”
Section: Introductionmentioning
confidence: 99%
“…Thiol-containing proteins could reduce the accumulation of ROS by oxidation of thiols, and played an important role in oxidative stability ( Cema zar et al, 2008;Hou ee-Levin & Berg es, 2008). Jiang et al (2018) examined the antioxidant capacity of eight thiol-containing compounds by electron spin resonance spectroscopy, and found that the activity of these compounds was significantly correlated with the amount of free sulfhydryl bonds presenting in the molecules. de Almeida et al (2013) reported that the concentration of thiol-containing peptides and proteins was relevant to the oxidative stability of beer, and the higher its content in beer, the stronger the oxidative stability of the beer.…”
Section: Introductionmentioning
confidence: 99%
“…Here we explore the UV photodissociation dynamics of methimazole (CAS number 60-56-0), also known as thiamazole and marketed as tapazole for use as an antithyroid drug for treating Graves' disease (hyperthyroidism). 48,49 Despite being commonly described as 2-mercapto-1methylimidazole (MMI) in the literature [50][51][52][53] and sold as such by chemical suppliers such as Sigma-Aldrich (product code 301507), methimazole exists in a tautomeric equilibrium (see figs. 1(c) and 1(d)).…”
Section: Introductionmentioning
confidence: 99%